Please help.
Question: Addmath (Quadratic Equations)
Given $\alpha$ and $\beta$ are the roots of the quadratic equation $2x^2 - 6x + 5 = 0$, form an quadratic equation with the roots $\alpha + 1$ and $\beta + 1$.
Please help.
Question: Addmath (Quadratic Equations)
Given $\alpha$ and $\beta$ are the roots of the quadratic equation $2x^2 - 6x + 5 = 0$, form an quadratic equation with the roots $\alpha + 1$ and $\beta + 1$.
$$x^2 - 3x + \frac 52 = (x - \alpha)(x - \beta) = x^2 - (\alpha + \beta)x + \alpha \beta$$
Then $\alpha + \beta = 3$ and $\alpha \beta = \frac 52$. So $$(x-(\alpha + 1))(x - (\beta + 1)) = x^2 - (\alpha + \beta+2)x +(\alpha \beta + \alpha + \beta + 1)$$
You should be able to do the rest.